DNA Barcode Characterization of Chocolate Hind Grouper (Cephalopholis boenak) in Several Indonesia Waters with the New Sequences Record from Madura Island - Abdul Basith; Abinawanto; Eni Kusrini; Yasman (HAYATI Journal of Biosciences, 2022)
This study aims to describe the molecular characteristics of DNA barcodes in chocolate hind grouper (Cephalopholis boenak) in Indonesian waters with new sequence records from Madura Island waters. Partial sequences of the cytochrome c oxidase 1 (CO1) gene were successfully obtained from two samples of C. boenak in Madura Island waters. In contrast, the other sequences were obtained from the BOLD system database, covering the Islands of Bali, Lombok, and Ambon waters. The overall molecular analysis involved 10 C. boenak sequences with a length of 625 bp. The results indicated that the population of C. boenak in Indonesia waters has high genetic diversity, as evidenced by the value of haplotype diversity (Hd) = 0.956 and nucleotide sequence diversity (Pi) = 0.01746, in which the population is distributed into eight haplotypes. Results of phylogenetic tree reconstruction of neighbor-joining and maximum-likelihood indicate similar topology. The branching of NJ and ML phylogenetic trees of C. boenak in Indonesia waters is grouped into two geographical clades. Clade 1 with the subpopulations of the waters from Madura, Bali, and Lombok Islands. Clade 2 with the subpopulations of the waters from Ambon Island. The results of the median-joining network reconstruction depicted a similar topology with both phylogenetic trees.